Influence of offence type and prior imprisonment on risk of death following release from prison: a whole-population linked data study - Jama-Alol, K.; Malacova, Eva; Ferrante, Anna; Alan, Janine; Stewart, Louise; Preen, D. (Taylor and Francis, 2015)
Purpose – The purpose of this paper is to examine the influence of offence type, prior imprisonment and various socio-demographic characteristics on mortality at 28 and 365 days following prison release. Design/methodology/approach – Using whole-population linked, routinely collected administrative state-based imprisonment and mortality data, the authors conducted a retrospective study of 12,677 offenders released from Western Australian prisons in the period 1994-2003. Cox proportional hazards regression was used to examine the association between mortality at 28 and 365 days post-release and offence type, prior imprisonment, and a range of socio-demographic characteristics (age, gender, social disadvantage and Indigenous status). Findings – Overall, 135 (1.1 per cent) died during the 365 days follow-up period, of these, 17.8 per cent (n=24) died within the first 28 days (four weeks) of their index release. Ex-prisoners who had committed drug-related offences had significantly higher risk of 28-day post-release mortality (HR=28.4; 95 per cent CI: 1.3-615.3, p=0.033), than those who had committed violent (non-sexual) offences. A significant association was also found between the number of previous incarcerations and post-release mortality at 28 days post-release, with three prior prison terms carrying the highest mortality risk (HR=73.8; 95 per cent CI: 1.8-3,092.5, p=0.024). No association between mortality and either offence type or prior imprisonment was seen at 365 days post-release. Originality/value – Post-release mortality at 28 days was significantly associated with offence type (with drug-related offences carrying the greatest risk) and with prior imprisonment, but associations did not persist to 365 days after release. Targeting of short-term transitional programmes to reduce preventable deaths after return to the community could be tailored to these high-risk ex-prisoners.